Pengaruh Kompensasi Dan Pengawasan Terhadap Efektivitas Kerja Pegawai Dinas Pemadam Kebakaran Kota Bekasi - Ade Haryuningsih Sari; Wahidin Septa Zahran; Renisya Ayu Utami (Jurnal Ilmu Administrasi Publik, 2022)
This study aims to analyze the effect of compensation and supervision on the work effectiveness of the employees at Fire Department Bekasi. In this study, the population of this study was employees of the Fire Department Bekasi. The sample of this research was 86 which is divided proportionally according to the work location (sector). Based on data analysis, the indicators in this study were valid and the variables were reliable. Based on the research, the regression equation obtained was: Y= 17.839 + 0.146 X1 + 0.384+ e. This equation shows that the variable of work effectiveness is influenced by compensation and supervision. The results of other studies conclude that compensation and supervision partially have an effect on the work effectiveness of the employees at the Fire Department Bekasi